Conversations: The Journal of Cavellian Studies 4 - Branco, Sérgio Dias (2016)
Literary cameos in this issue include Jane Austen, Charles Baudelaire, Marcel Proust, and Samuel Beckett (and no Shakespeare, a relief to some, a scandal to others).